A law describing the distribution of syllables in the words from dictionaries - Merkytė, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Мерките. Закон, описывающий распределение слогов в словах словарей R. Merkytė. Skiemenų pasiskirstymo žodžiuose iš žodynų dėsnis